2008
DOI: 10.1007/s00268-008-9827-y
|View full text |Cite
|
Sign up to set email alerts
|

Which Method Should We Select for Pancreatic Anastomosis After Pancreaticoduodenectomy?

Abstract: Background This study was designed to compare surgical, morphological, and functional outcomes of pancreaticoduodenectomy (PD) according to the types of pancreaticoenterostomy performed and to suggest a proper anastomotic method after PD. Methods From January 2001 to December 2006, 147 PDs were performed at Ajou University Medical Center. Surgical, morphological, functional, and nutritional outcomes after PD were retrospectively compared according to the types of management of pancreatic remnant and whether pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 23 publications
(40 reference statements)
2
23
0
1
Order By: Relevance
“…The incidence of clinically significant POPF (12.2%) in our cohort of distal pancreatectomies is consistent with the 12% incidence of grade B/C POPF reported by Nathan et al [2] in a series of 704 distal pancreatectomy cases and by Kleeff et al [23 ]in a series of 302 distal pancreatectomy cases as well as with the 16% POPF rate in 462 distal pancreatectomy cases reported by Ferrone et al [7]. The incidence of clinically significant POPF in our patients with pancreatoduodenectomy is with 2.6% quite low and corresponds well to the results of Büchler et al [29] (2.1%) and Kim et al [30] (3.2%) who used a similar technique of duct-to-mucosa pancreatico-jejunal anastomosis. Our data confirm the observation of Pratt et al [25] that a substantial number of clinically significant POPF present as latent fistulas.…”
Section: Discussionsupporting
confidence: 75%
“…The incidence of clinically significant POPF (12.2%) in our cohort of distal pancreatectomies is consistent with the 12% incidence of grade B/C POPF reported by Nathan et al [2] in a series of 704 distal pancreatectomy cases and by Kleeff et al [23 ]in a series of 302 distal pancreatectomy cases as well as with the 16% POPF rate in 462 distal pancreatectomy cases reported by Ferrone et al [7]. The incidence of clinically significant POPF in our patients with pancreatoduodenectomy is with 2.6% quite low and corresponds well to the results of Büchler et al [29] (2.1%) and Kim et al [30] (3.2%) who used a similar technique of duct-to-mucosa pancreatico-jejunal anastomosis. Our data confirm the observation of Pratt et al [25] that a substantial number of clinically significant POPF present as latent fistulas.…”
Section: Discussionsupporting
confidence: 75%
“…Overall, 26 articles describing 3,752 patients were identified for the meta-analysis: 22 OCSs (n = 3, 199 patients) [35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56] and 4 RCTs (n = 553 patients) [10,57,58,59]. A total of 1,922 patients underwent PG (RCTs n = 276 patients, OCSs n = 1,646 patients), whilst 1,830 patients underwent PJ (RCTs n = 277 patients, OCSs n = 1,553 patients).…”
Section: Resultsmentioning
confidence: 99%
“…One retrospective, single-institution study revealed a 3.2% rate of POPF in the DmPJ group and a rate of 17.5% in its IPJ group without significant mortality differences. 18 One dual-institution controlled trial, however, found an odds ratio (OR) of 2.4 for POPF incidence between DmPJ and IPJ, again without significant mortality differences. 6 Still, other studies have reported minimal to no difference in risk of fistula formation or mortality.…”
Section: Introductionmentioning
confidence: 99%